Volatile compounds in different parts of the fruit Psidium guajava L. cv. "Media China" identified at distinct phenological stages using HS‐SPME‐GC‐QTOF/MS. Issue 6 (17th July 2018) - Elizalde‐González, María P.; Segura‐Rivera, Erika J.
Abstract: Introduction: Determination of the volatile organic compounds (VOCs) emitted by immature fruits furthers our understanding of plant–pest interactions and by fruits in a ripe state concerns food quality. Objectives: To apply headspace solid‐phase microextraction gas chromatography quadrupole time‐of‐flight mass spectrometry (HS‐SPME‐GC‐QTOF/MS) to compare the volatiles emitted by different parts of guava ( Psidium guajava L . cv. "Media China") at different maturation stages. Methodology: HS‐SPME combined with GC‐QTOF/MS was used to characterise the VOCs of entire guavas in the orchard and under laboratory conditions. For chemical analysis X‐ray fluorescence spectroscopy, refractometry, titration, complexometry, diode array detector high‐performance liquid chromatography (DAD‐HPLC) and refractive index detector (RI)‐HPLC were used. Results: The guava variety was rich in potassium and poor in sodium. A total of 44 VOCs were identified in different phenological stages and parts of the fruits. Release of VOCs was influenced by the temperature in the plantation, and transformation of innate fruit VOCs started immediately after cutting. Conclusion: The most abundant VOC released by the immature fruit in the plantation overnight was ( S )‐limonene, and it concentrated in the outer skin (pericarp). The esters ethyl benzoate, ethyl octanoate, butyl‐2‐methylbutanoate, ethyl hexanoate, cis ‐3‐hexenyl acetate, and ethyl butanoate were emitted by ripe whole fruits. During ripening ethyl benzoate reached a maximum production after three to five days, while the formation of the aldehydes benzaldehyde, hexanal and trans ‐2‐hexen‐1‐al started thereafter. Abstract : 44 volatile organic compounds were identified in different phenological stages and parts of Psidium guajava L. cv. "Media China" by HS‐SPME‐GC‐QTOF‐MS. (S)‐limonene concentrates in the pericarp of immature fruit and is released in the plantation overnight. During ripening ethyl benzoate reaches a maximum production after three to five days.